PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU USAHA YANG MENJUAL PRODUK PANGAN IMPOR TANPA IZIN EDAR MELALUI TOKO ONLINE (STUDI PUTUSAN NO 613/PID.SUS/2019/PN.PDG) - Christopher Christopher; Rugun Romaida Hutabarat (Jurnal Hukum Adigama, 2021)
In this modern era, technological developments are increasingly advanced and growing rapidly, because of these technological advances, it supports transactions through online shops, causing some business actors who sell goods and services both domestically and abroad who do not have a license. certain of the goods it sells. And these goods have been circulated and traded freely, so that business actors can sell goods with high competitiveness both domestically and abroad. Even the existence of free trade can have a negative impact on those who have bought it. Therefore, there must be the application of criminal liability to business actors who have committed criminal acts by selling products in the form of goods or services that violate an applicable provision. Based on the results of the analytical research in Decision No. 613/Pid.Sus/2019/Pn.Pdg, the perpetrator can be imposed with criminal sanctions because he has fulfilled one of the elements, namely the ability to be responsible for all his actions. In criminal liability which is one of the other requirements is the element of ability to be responsible for a criminal act. So every criminal act in the Criminal Code can generally be described into two types, namely subjective and objective elements. Based on the judge's consideration in Decision No. 613/Pid.Sus/2019/Pn.Pdg, the defendant should be sentenced to a fine because the defendant's actions clearly harm the state in terms of non-tax state income or abbreviated.